Penerapan Website untuk Digitalisasi dan Pengembangan Bisnis di Usaha Pemandian Air Panas Karunia Sipoholon - Rudy Chandra; Tegar Arifin Prasetyo; Tahan HJ Sihombing; Juan Carlos Munthe; Christian Benedict Lumbantoruan; Dame Sisri Haryati Katarina Rumapea; Herbeth Augustinus Napitupulu (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2024)
Traveling is an activity that people do to unwind from their daily routines. There are many types of travel destinations, and one of them is a natural hot spring located in Situmeang Habinsaran Village, Sipoholon District, North Tapanuli. Besides being a tourist destination, natural hot springs are believed to have the ability to cure various skin diseases and promote healthier skin. The owner of the Karunia hot spring business is one of the entrepreneurs who provide hot spring baths, accommodations/homestays, and a restaurant. This business opportunity has become more competitive with many similar ventures opening up. Marketing and promoting this natural attraction continues. As time goes by, the promotion and business systems need to be enhanced by using information technology to improve. A website is one of the means for promotion and branding, enabling the digitization of the established business. Building a website is applied for promotional purposes and to enhance credibility with the public, making them more familiar with the hot spring tourism in Sipoholon, especially Karunia hot spring. The website also serves as a centralized platform for financial management, cash flow, and business operations, which have previously been done manually. The goal of creating this website is for partners to increase income and improve business branding